Understanding Heads of Academic Departments’ leadership styles and lecturers’ job satisfaction: improving human resource development in Research Universities. - Sadeghi, Amir; Lope Pihie, Zaidatol Akmaliah; Elias, Habibah; Foo , Say Fooi (2011)
Using MLQ and WFJSDS as instruments this quantitative study found that heads of departments exhibited combination of transformational, transactional, and laissez-faire leadership styles. They showed transformational leadership fairly often and transactional leadership sometimes which are in line with MLQ norm. While they exhibited laissez-faire leadership behavior once in a while this is not consistent with MLQ norm. Lecturers’ displayed moderate level of job satisfaction. Transformational leadership was dominant predictor of job satisfaction.